The receptor tyrosine kinase Off-track is required for layer-specific neuronal connectivity in Drosophila. - Cafferty, P.; Yu, L.; Rao, Y. (Development, 2004)
The nervous system in many species consists of multiple neuronal cell layers, each forming specific connections with neurons in other layers or other regions of the brain. How layer-specific connectivity is established during development remains largely unknown. In the Drosophila adult visual system, photoreceptor (R cell) axons innervate one of two optic ganglia layers; R1-R6 axons connect to the lamina layer, while R7 and R8 axons project through the lamina into the deeper medulla layer. Here, we show that the receptor tyrosine kinase Off-track (Otk) is specifically required for lamina-specific targeting of R1-R6 axons. Otk is highly expressed on R1-R6 growth cones. In the absence of otk, many R1-R6 axons connect abnormally to medulla instead of innervating lamina. We propose that Otk is a receptor or a component of a receptor complex that recognizes a target-derived signal for R1-R6 axons to innervate the lamina layer.